Identification of Potential Immune-Related circRNA–miRNA–mRNA Regulatory Network in Intestine of Paralichthys olivaceus During Edwardsiella tarda Infection - Xiu, Yunji; Jiang, Guangpeng; Zhou, Shun; Diao, Jing; Liu, Hongjun; Su, Baofeng; Li, Chao (Frontiers in Genetics, 2019)
Olive flounder (Paralichthys olivaceus) is an important economical flatfish in Japan, Korea and China, but its production has been greatly threatened by disease outbreaks. In this research, we aimed to explore the immune responsive mechanism of P. olivaceus against Edwardsiella tarda infection by profiling the expression of circRNA, miRNA and mRNA by RNA-seq, and constructing a regulatory circular circRNA-miRNA-mRNA network. Illumina sequencing of samples from normal control (H0), 2 h (H2), 8 h (H8) and 12 h (H12) post-challenge was conducted. Differentially expressed (DE) circRNA (DE-circRNAs), miRNAs (DE-miRNAs), and mRNAs (DEGs) between challenge and control groups were identified, resulting a total of 62 DE-circRNAs, 39 DE-miRNAs and 3,011 DEGs. Based on the differentially expressed gene results, miRNA-target interactions (circRNA-miR¬NA pairs and miRNA-mRNA pairs) were predicted by miRanda software. Once these paired were combined, a preliminary circRNA-miRNA-mRNA network was generated with 198 circRNA-miRNA edges and 3,873 miRNA-mRNA edges, including 44 DE-circRNAs, 32 DE-miR¬NAs, and 1,774 DEGs. KEGG analysis was performed to evaluate the function of the DEGs in this network, and we focused and identified two important intestinal immune pathways (Herpes simplex infection and Intestinal immune network for IgA production) that showed statistical significance between the challenge and control groups. Furthermore, three critical DEGs (nectin2, MHC II α-chain and MHC II β-chain) were identified, mapped into the preliminary circRNA‑miRNA‑mRNA network and new circRNA-miRNA-mRNA regulatory networks were constructed. In conclusion, we for the first time identified circRNA-miRNA-mRNA network from P. olivaceus in the pathogenesis of E. tarda, and provided valuable resources for further analyses of the molecular mechanisms and signaling networks.